Strategi Komunikasi Digital dalam Pemasaran: Studi Peran Media Sosial dalam Keputusan Pembelian Konsumen - Rosalia, Dian (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The advancement of digital technology has transformed the marketing landscape, positioning social media as a key channel in digital communication strategies. This study aims to examine the impact of social media on consumer purchasing decisions, the factors influencing the effectiveness of digital communication strategies, and the role of social media platforms in fostering customer loyalty. Using a qualitative approach, data were collected through in-depth interviews with business practitioners and consumers, complemented by a literature review. The findings reveal that social media significantly influences consumer purchasing decisions, primarily through targeted advertising, customer reviews, and direct brand-user interactions. The effectiveness of digital communication strategies is determined by key factors such as marketing content, customer engagement, the role of influencers, and the use of paid advertisements. Moreover, the study finds that platforms like Instagram, TikTok, and YouTube outperform Facebook and Twitter in building customer loyalty due to their highly interactive features and superior content personalization. These findings underscore the importance of integrating organic and paid strategies in digital marketing, as well as selecting social media platforms that align with the target market’s characteristics. This study contributes to the academic discourse on social media’s role in digital marketing while providing practical insights for businesses seeking to optimize their digital communication strategies.